Другая женщина: [роман] / Евгения Перова - Перова Евгения Георгиевна (Счастье мое, постой!, 2016)
Экземпляры: ф.4 (20220725) / Инвентарный номер: 982 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 27 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44